2021
DOI: 10.3390/biology10050372
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of Ozonated Oils for the Treatment of MRSA Skin Infection in an Animal Model of Infected Ulcer

Abstract: Diabetic foot ulcers are a common cause of morbidity in diabetic patients. One of the main pathogens found in these ulcers is methicillin-resistant Staphylococcus aureus (MRSA). MRSA often carries resistance to several classes of antibiotics and their infections are becoming harder to treat. Therefore, new alternatives are urgently needed. Thus, this study aimed to investigate the capacity of topical ozonated oil application on the treatment of early-stage skin infected with MRSA in an animal model. Ozonated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
(54 reference statements)
1
10
0
Order By: Relevance
“…Therefore, the data presented herein indicate that the use of ozonized water in technologies for the disinfection of surfaces, medical instruments, and even humans may be an alternative and reliable approach to delay or stop the spread of microbes, as discussed by a recently published patent prospecting [11]. Ozone therapy has been indeed effective not only in dentistry but also in endocrinology and physical therapy [24,67,73,[77][78][79][80][81], leading, in some cases, to the control of microbial infections while treating other illnesses [53,79,82]. Even methicillin-resistant S. aureus have been killed by O 3 dissolved in oil during an experimental model of infected ulcer [53].…”
Section: Microbials' Morpho-structural Changes Upon Incubation Of Ozonized Tap Watermentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, the data presented herein indicate that the use of ozonized water in technologies for the disinfection of surfaces, medical instruments, and even humans may be an alternative and reliable approach to delay or stop the spread of microbes, as discussed by a recently published patent prospecting [11]. Ozone therapy has been indeed effective not only in dentistry but also in endocrinology and physical therapy [24,67,73,[77][78][79][80][81], leading, in some cases, to the control of microbial infections while treating other illnesses [53,79,82]. Even methicillin-resistant S. aureus have been killed by O 3 dissolved in oil during an experimental model of infected ulcer [53].…”
Section: Microbials' Morpho-structural Changes Upon Incubation Of Ozonized Tap Watermentioning
confidence: 84%
“…The antimicrobial action of O 3 herein showed is related to its powerful oxidizing action. O 3 has been widely used as an antimicrobial, in both its gaseous and aqueous form, due to its wide range of microbiological, cleaning, and metabolic activities [6,13,15,16,24,34,45,52,53]. The antimicrobial action of O 3 is related to its powerful oxidizing action.…”
Section: Biocidal Effect Of Ozonized Tap Watermentioning
confidence: 99%
See 1 more Smart Citation
“…This arrested state of necrosis associated with an inflammatory microenvironment hindered healing progression, representing key hallmarks of wound chronicity [ 2 , 4 ]. Ultimately, this model depicts critical features of the DFI microenvironment that previous animal models of infected wounds failed to validate, including: i) the ability of MRSA to penetrate and spread within the wound bed, rather than being restricted to the scab [ 12 15 ]; ii) minimizing primary skin contraction that naturally occurs in rodents, which allows a healing mechanism by re-epithelization [ 12 , 14 , 16 , 17 ]; and iii) control over the causative agent and dose of infection, circumventing the lack of standardization observed in models of naturally infected wounds that depend on housing conditions, source of animal colonies and host skin microbiome [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the application of ozone in medicine and dentistry has particularly increased because of its several recognized benefic actions. Much research has demonstrated a broad-spectrum antimicrobial activity for ozonized water/oils against bacteria, virus, protozoa, and fungi [1][2][3][4][5]. Additionally, many other properties have been attributed to ozone, such as immunomodulant, anti-hypoxic, anti-inflammatory, and regenerative ones [6,7].…”
Section: Introductionmentioning
confidence: 99%